(untitled) (Research, Society and Development, 2022)
Toxoplasmosis is a parasitic disease that, when acquired during pregnancy can be transmitted to the fetus, being asymptomatic, causing sequelae to the newborn or leading to fetal death. Thus, this retrospective, quantitative and observational work analyzed data from pregnant women diagnosed with toxoplasmosis, in outpatient care during the years 2015 to 2019, in the city of Cascavel-PR. This study sought to analyze the efficiency of the drugs (Spiramycin, Pyrimethamine, Sulfadiazine and Folinic Acid), establish the result of the newborns’ serology, in addition to obtain sociodemographic data of these pregnant women, analyzing age, marital status and education level. Fisher’s statistical test was used, with a significance level of α <0,05. In this study, pregnant women who did not use medication had 8.63 times the chance (p <0,01) of an unfavorable outcome compared to those who underwent complete treatment. Therefore, the importance of performing early prenatal care and performing the correct treatment for gestational Toxoplasmosis is highlighted.